Pendidikan Karakter Dalam Sekolah Taman Seminari - Adison Adrianus Sihombing (Badan Litbang dan Diklat Kementerian Agama RI, 2021)
AbstractThis article aims to examine the application of character education in Taman Seminary, the level of early childhood education. The research was conducted at five schools in the Java region in March – August 2019 using qualitative methods. The result shows that the school under the guidance of the Directorate General of Catholic Community Guidance has a positive impact on the growth and development of children's character. Children begin to be independent by eating alone, can make a cross, pray spontaneously before eating, and even children can remind their parents if they forget to pray before eating. This is evident from the recognition of the parents who see changes in the attitudes and behavior of religious, independent, disciplined, and caring. This research recommends that the Directorate General of Catholic Community Guidance make a grand design for the Taman Seminary school and conduct socialization to the public, specifically to the hierarchy of the Catholic Church, so that this policy has full support. In addition, substantial efforts and actions are needed to increase the competence of teaching staff and improve facilities and infrastructure, including class buildings.AbstrakArtikel ini bertujuan untuk mengkaji penerapan pendidikan karakter di Taman Seminari, jenjang pendidikan anak usia dini. Riset dilakukan pada lima sekolah di regio Jawa pada Maret – Agustus 2019 dengan menggunakan metode kualitatif. Temuannya adalah ternyata sekolah yang berada dalam binaan Ditjen Bimas Katolik ini berdampak positif terhadap pertumbuhan dan perkembangan karakter anak. Anak mulai mandiri dengan makan sendiri, dapat membuat tanda salib, berdoa spontan sebelum makan, bahkan anak dapat mengingatkan orang tuanya jika lupa berdoa sebelum makan. Hal ini terbukti dari pengakuan orang tua siswa yang melihat adanya perubahan sikap dan perilaku anak yang religius, mandiri, disiplin, peduli. Riset ini merekomendasikan agar Ditjen Bimas Katolik membuat grand design sekolah Taman Seminari dan melakukan sosialisasi kepada publik, secara khusus kepada hierarki Gereja Katolik sehingga kebijakan ini mendapat dukungan penuh. Selain itu diperlukan usaha dan tindakan konkret untuk peningkatan kompetensi tenaga pengajar dan perbaikan fasilitas sarana-prasarana termasuk gedung kelas.